Effectiveness of breast massage for the treatment of women with breastfeeding problems: a systematic review. (August 2019) - Anderson, Loretta; Kynoch, Kathryn; Kildea, Sue; Lee, Nigel
ABSTRACT: Objectives: The aim of this systematic review was to identify the effectiveness of breast massage as a treatment for women with breastfeeding problems. More specifically, the objective was to identify if breast massage as an intervention led to less pain or increased milk supply, or assisted in a reduction or resolution of blocked ducts, breast engorgement and mastitis. Introduction: Breastfeeding protects babies against many illnesses, and the health benefits for women have been well documented. However, breastfeeding rates steadily drop to approximately 15% by six months, which is the World Health Organization's recommended length of time for exclusive breastfeeding. Breastfeeding problems such as blocked ducts, breast engorgement and mastitis are major complications attributing to the decline in breastfeeding rates. Breast massage may relieve pain and resolve symptoms associated with conditions that contribute to discontinued breastfeeding. Inclusion criteria: This review considered both experimental and epidemiological study designs and included breastfeeding women of any age, parity or geographical location. The types of interventions considered for inclusion were any type of breast massage that was offered to women for breastfeeding problems. Comparators included the usual care provided to women with breastfeeding problems. Primary outcomes of interest were an increase in breast milk supply, reduction of breast pain, and symptom resolution of blocked ducts, engorgement and mastitis. Secondary outcomes included duration of breastfeeding. Methods: Studies published from 1980 to 2017 in English and Japanese were considered for inclusion in this review. The databases searched with the majority of results included CINAHL, Cochrane Library, Embase, PubMed, Science Direct, Scopus and Web of Science. Search for unpublished studies included Google Scholar, ClinicalTrials.gov and ProQuest Dissertations and Theses. Results: There were six studies included in this review: three randomized controlled trials and three quasi-experimental studies. There was considerable heterogeneity of study outcome measures, and the use of unvalidated tools in many of the studies led to the inability to pool the results. Furthermore, the heterogeneity of the interventions themselves coupled with small sample sizes for each study greatly decreased generalizability of the outcomes and reduced the overall effectiveness of the interventions. However, all included studies reported a reduction in pain regardless of the breast massage technique used. Overall, varying types of breast massage were helpful in reducing immediate pain and resolving symptoms. Conclusions: Overall, different types of breast massage were reported as effective in reducing immediate pain for the participants. However, the lack of detailed explanation of the breast massage technique and the extensive training needed to undertake the breast massage decrease the ability to replicate the results. These outcomes may be useful for healthcare professionals caring for women with breastfeeding problems. Future research needs include validating a universal measurement tool for breastfeeding problems and the need for more robust randomized controlled trials, particularly in vulnerable groups such as mothers of preterm infants. Longer follow-up periods are also suggested to establish if breast massage impacts breastfeeding duration.